Kakovost površinskih voda v vodnogospodarskih strokovnih podlagah za potrebe usklajevanja prostorskega planiranja - Vahtar, Marta (Acta hydrotechnica, 2000)
Properly planned and presented elements of water management studies and plans, to be used in the harmonization process in spatial planning, are the most efficient way of including these elements into the procedure of spatial harmonization. At the same time, properly planned water management studies andplans for the needs of spatial planning can also be an efficient way of introducing the immission criteria of water safety. Water management studies and plans for the preparation of the State Spatial Master Plan have, so far, not presented these elements in the most appropriate way. In order to bridge this situation at least partially, new water management studies and plans are being prepared to be used for the needs of the State Spatial Master Plan of the Republic of Slovenia. They will be presented in two layers. The first graphic layer will show the present situation of the system in the space, while the second graphic layer will show the conditions of use expressed through the necessary precautions for achieving long-term vision. The paper shows how the elements of surface water quality are presented and included in the preparation of the State Spatial Master Plan
Keywords: kakovost vode; prostorsko planiranje; spatial planning; surface water quality protection; varstvo kakovosti površinskih voda; vodno gospodarstvo; water management; water quality